Vegetable gardening: Boon for Agri-farmers of Punjab - Jadoun, Y S; Singh, Kulbir (Indian Farming, 2022)
Jagtar Singh serves as a perfect example for the promotion of nutritional/vegetable gardening venture. He has not only created livelihood as well as nutritional security for himself but also motivated other beneficiary as well as non-beneficiary farmers of the operational area. He serves as a role model for small and marginal farmers who can earn lots of profit from adopting this lucrative and profit making venture. He is also providing desired knowledge and skills regarding vegetable gardening to the fellow farmers who are new in this venture by guiding them and showing the results on his demonstration farm. He is making good efforts so that more and more number of fellow farmers of his village or nearby villages are able to adopt this intervention as an entrepreneurial venture and can earn more and more profit from this exemplary enterprise.